La disolución de las identidades en la cultura contemporánea : (intento de explicación histórico-filosófica) - Mosto, Marisa (Sapientia, 2006)
This article ponders about the subject of the dissolution of the identities from different points of view: 1) From a philosophical historical point of view presenting a tradition of the modern and contemporary thought that develops a negative conception of the essential limits. 2) From the perspective of the reduction of the human reason to the instrumental reason and its relation with the loss of the aura, the loss of the sacred, mystic perspective of what is real, and the conversion of all value to the value of change. 3) The contribution of the socioeconomic organization and the forms of work and leisure to the blurring of the human face. Finally, it analyzes strategies for the recovery of the perception of the entity's qualities.